Identification of potentially druggable molecular alterations in skin adnexal malignancies. Issue 6 (30th April 2019) - Cavalieri, Stefano; Busico, Adele; Capone, Iolanda; Conca, Elena; Dallera, Elena; Quattrone, Pasquale; Licitra, Lisa; Pruneri, Giancarlo; Bossi, Paolo; Perrone, Federica
Abstract: Skin adnexal cancers (SAC) are a heterogeneous group of rare malignancies with histological differentiation towards epithelial adnexa, which lack effective systemic treatments. The aim of this work is to identify any potentially druggable genomic alterations for possible targeted therapies. Cases of primary or recurrent/metastatic (RM) SAC between 2002 and 2014 were identified by searching the institutional cancer registration database. Histological sections of all referral cases were reviewed by a dedicated pathologist to confirm diagnosis. Immunohistochemistry was performed to assess the expression of androgen receptors (AR) and human epidermal growth factor receptor type 2 (HER2). Targeted next‐generation sequencing (T‐NGS) was performed to identify targetable mutations (panel of 50 genes analyzed by Cancer Hotspot Panel, Ion‐Torrent Personal Genome Machine). Mutational analysis of the PTCH1 gene not present in the T‐NGS panel was assessed by Sanger sequencing. A total of 45 cases with available histological samples were identified (35 primary, 10 RM). The most frequent histological type was porocarcinoma ( n = 12). Globally, 14 cases (31%) were AR+ (6/10 RM, 60%; 8/35 primary, 23%). HER2 was shown as 2+ in eight of 42 (19%) cases (2/9 RM, 22%; 6/33 primary, 18%). DNA was adequate for T‐NGS analysis in 25 cases. In the majority of cases (17 cases, 68%) at least one mutation in oncogenes or tumor suppressor genes was found: the most frequent ones involved TP.53 (13 cases, 76% of mutated SAC) and PIK3CA (three cases, 18%). The rate of PTCH1 mutation was 30%. These findings support the use of molecular screening in patients with advanced SAC.